ANALISIS NILAI-NILAI PANCASILA DALAM MAKNA SIMBOL GERAK TARIAN TORTOR PADA UPACARA PERKAWINAN BATAK TOBA DI KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Dormina, Dormina; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this event will be based on Research by the traditions of the societies conducted by Tortor Subdistrict Tambusai Rokan Hulu. Formulation of the problem in this research is whether there are values of Pancasila symbol meaning in motion dance Tortor at Toba Batak Marriage in Upacra Subdistrict Tambusai Rokan Hulu. His goal was to find out the values of Pancasila symbol meanings contained in the motion dance tortor at Toba Batak Marriage Ceremony in district Tambusai Rokan Hulu. In January of 2019 until February 2019. This research is a descriptive qualitative become respondents in this study were respondents chosen by purposive sampling as required. As for the respondents examined are as follows: the Chairman of the customs, public figures, and batak communities that exist in district Tambusai. Using data collection techniques: observation, documentation, interviews, now with engineering data analysis. Using techniques of data analysis: data collection, classify the answers reponden, determine the large percentage of alternative answers of respondents using the formula P = f/n x 100% present in the form of tables, and draw conclusions. Based on the results of the study show that there are values of Pancasila was the fifth sila i.e., divinity of the one true God, just and civilized humanity, the unity of Indonesia, led by populist wisdom wisdom in consultative representation and social justice for all the people of Indonesia. Based on the recapitulation of the first sila is the amount of data the most high are answered by the respondent and the third sila sila sila is four and the lowest are answered by the respondents, Pancasila values contained in tortor tradition in district Tabusai Rokan Hulu.Key Words: Values Of Pancasila, Tortor